Parasites of the grouper fish Epinephelus coioides (Serranidae) as potential environmental indicators in Indonesian coastal ecosystems - Kleinertz, Sonja; Palm, H.W.; Justus Liebig University Giessen (My University, 2015)
A total of 195 Epinephelus coioides (Hamilton, 1822) were studied for fish parasites from Javanese (Segara Anakan lagoon) and Balinese waters. Up to 25 different parasite species belonging to the following taxa: one Ciliata, one Microsporea, five Digenea, one Monogenea, four Cestoda, four Nematoda, one Acanthocephala, one Hirudinea and seven Crustacea were identified with four new host and locality records. The dominant parasites included the monogenean Pseudorhabdosynochus lantauensis (53.3-97.1%), the nematode Spirophilometra endangae (23.3-42.9%), the digenean Didymodiclinus sp. (2.9-40.0%), the nematodes Philometra sp. (22.6-34.3%) and Raphidascaris sp. (2.9-28.6%), and the isopod Alcirona sp. (6.7-31.4%). Regional differences for E. coioides were found in terms of endoparasite diversity, total diversity according to Shannon Wiener, Simpson index and Evenness. A comparison with published data from Sumatera revealed highest endoparasite diversity (Shannon Wiener: 1.86/1.67-2.04) and lowest ectoparasite/endoparasite ratio (0.73/0.57-0.88) off the Balinese coast, followed by Lampung Bay, Sumatera (1.84; 0.67), off the coast of Segara Anakan lagoon (1.71; 0.71), and in the lagoon (0.30/0.19-0.66; 0.85/0.67-1.00). The presented data demonstrate the natural range of these parameters and parasite prevalences according to habitat and region, allowing adjustment of the scale that has been used in the visual integration of the parasite parameters into a star graph. The parasite fauna of E. coioides in Segara Anakan lagoon ´improved´ from 2004 until 2008/09, possibly related to earlier oil spill events in 2002 and 2004. The use of grouper fish parasites as an early warning system for environmental change in Indonesian coastal ecosystems is discussed.
Keywords: ddc:630